นิติสำนึกของผู้ปกครองบุคคลออทิสติก - จิรายุพร รัตนประดิษฐ์ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2017)
People with autism are classified as disabled by Ministry of Social Development and Human Security’s Announcement about the categories and criteria of disability B.E.2555. According to the law for people with disability, which has many laws involved, autistic people are able to get any benefits and welfare as disabled. This seems to be beneficial for people with autism; however, the number of autistic people applying for disabilities ID cards is a few if compared to the whole number of them across the country. I, therefore, wish to study legal consciousness of autistic people’s parents due to parents are legally obligated to take care of their children. To find out the awareness and attitude of the parents toward the law and whether the law plays a role in everyday lives of people with autism. Researcher used the framework of legal consciousness by in-depth interviews with autistic people’s parents. The interviewees recounted past experiences, and researcher took control of the narrative and interviews within the framework of the research. The questions to be asked didn’t mention provisions of law directly or frame laws relating to the research too narrow. However, the researcher would find legal issues that were raised by the interviewees during the interviews. After that, the collecting data were analyzed and the findings would be presented in the form of descriptive content. In addition, the researcher would present the findings about legal consciousness of autistic people’s parents to achieve the purpose of this research. The results showed that the main reason for most parents who bring their children to register for disabilities ID cards is they think this law will provide coverage for their children if their children break the law by unconsciousness and their children must have this right. While the benefits of the registration is lesser role for high-income parents; on the other hand, it is more role for low-income parents, and they also expect more rights and benefits since it is not enough. Some parents believe that the registration for disabilities ID cards will make a guilt on the children's future. As children young age, parents expect that children will be better and will not be seen as a social disability. Although the legislation focus more on people with autism, but in reality how people with autism can get their rights by law depends on legal consciousness of autistic people’s parents. In addition, the state should play a role in providing support to the parents when their children are in young age because there is a better chance for young age people with autism to make a great development in tactics for taking care of themselves; to reduce the burden of parents and reduce the government's budget in the future.